C‐C motif chemokine ligand 5 confines liver regeneration by down‐regulating reparative macrophage‐derived hepatocyte growth factor in a forkhead box O 3a–dependent manner. Issue 6 (5th May 2022) - Huang, Miao; Jiao, Junzhe; Cai, Hao; Zhang, Yichi; Xia, Yuhan; Lin, Jiacheng; Shang, Zhi; Qian, Yihan; Wang, Fang; Wu, Hailong; Kong, Xiaoni; Gu, Jinyang
Abstract: Background and Aims: Liver regeneration (LR) is vital for the recovery of liver function after hepatectomy. Limited regeneration capacity, together with insufficient remnant liver volume, is a risk factor for posthepatectomy liver failure (PHLF) resulting from small‐for‐size syndrome. Although inflammation plays an important role in controlling LR, the underlying mechanisms still remain obscure. Approach and Results: We identified C‐C motif chemokine ligand (CCL) 5 as an important negative regulator for LR. CCL5 levels were elevated after partial hepatectomy (PHx), both in healthy donors of living donor liver transplantation (LT) and PHx mouse models. Ccl5 knockout mice displayed improved survival after 90% PHx and enhanced LR 36 h after 70% PHx. However, primary hepatocytes from Ccl5 −/− mice exposed to growth factors in vitro showed no proliferation advantage compared to those from wild‐type (WT) mice. Flow cytometry analysis showed that proportions of Ly6C lo macrophages were significantly increased in Ccl5 −/− mice after 70% PHx. RNA‐sequencing analysis revealed that sorted macrophages (CD11b + Ly6C lo&hi ) manifested enhanced expression of reparative genes in Ccl5 −/− mice compared to WT mice. Mechanistically, CCL5 induced macrophages toward proinflammatory Ly6C hi phenotype, thereby inhibiting the production of hepatocyte growth factor (HGF) through the C‐C motif chemokine receptor (CCR) 1– and CCR5‐mediated forkhead box O (FoxO) 3a pathways. Finally, blockade of CCL5 greatly optimized survival and boosted LR in the mouse PHx model. Conclusions: Our findings suggest that inhibition of CCL5 is a promising strategy to improve regeneration restoration by enhancing HGF secretion from reparative macrophages through the FoxO3a pathway, which may potentially reduce the mortality of PHLF. Abstract : Schematic diagram of CCL5 downregulating reparative macrophage‐derived HGF in a FoxO3a dependent manner after PHx. Increased CCL5 secretion from either hepatocytes or non‐hepatocytes may impede Hgf transcription in reparative macrophages via CCR1‐ and CCR5‐mediated FoxO3a signaling instead of NF‐κB at the proliferation phase when subjected to PHx.image